2022
DOI: 10.3389/fpsyg.2022.914484
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 certificate as a cutting-edge issue in changing the perception of restaurants’ visitors—Illustrations from Serbian urban centers

Abstract: As one of the first European cases of the introduction of COVID-19 certificates, the Serbian Government initiated the measure of limited working hours of restaurants for unvaccinated visitors. Due to such actions and frequent bans on working during the pandemic, many restaurants in Serbia had to lay off workers or close. At the end of October 2021, the certificate for entering restaurants and all catering facilities for all the visitors became mandatory. It is interesting to note that earlier findings suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…For those employees whom they still hired, the downtime during the pandemic gave them time to refresh or improve their skills by attending various training programs. Additionally, this study also found that to reduce the risk of tourists within the uncertainty situation, health measure should be emphasized in all tourism businesses to increase tourists' confidence and purchase intention [64].…”
Section: Theoretical Contributionsmentioning
confidence: 65%
“…For those employees whom they still hired, the downtime during the pandemic gave them time to refresh or improve their skills by attending various training programs. Additionally, this study also found that to reduce the risk of tourists within the uncertainty situation, health measure should be emphasized in all tourism businesses to increase tourists' confidence and purchase intention [64].…”
Section: Theoretical Contributionsmentioning
confidence: 65%
“…We have had to face tragedies, economic damage, and permanent change both as individuals and as a society. The pandemic has had a major impact on consumer behavior (Gajić et al, 2022) and on the world of work (de Alves et al, 2021). While some employees have lost their jobs and some organizations have gone bankrupt (Nicola et al, 2020), other organizations have begun to adopt new approaches.…”
Section: Discussion Limitations and Future Workmentioning
confidence: 99%
“…Future surveys could be undertaken across cultures and nations (e.g., domestic visitors vs. overseas tourists) in order to acquire data samples, which would better support the stability of the study’s model. Moreover, according to Gajić et al (2022a) , obtaining COVID-19 certificates of these industrial heritage attractions is likely to reduce the tourists’ fear of pandemic, therefore future studies could explore the effect of COVID-19 certificates on tourists’ authentic experience and Environmentally Responsible Behaviors.…”
Section: Discussionmentioning
confidence: 99%